Speech, Language and Cognitive Profile of Mild Cognitive Impairment: A single Case Study - Bhattarai, Biraj; K B, Joanna; P Niranjana; B P, Abhishek (Nepalese Medical Journal, 2021)
Heterogeneity of symptoms within and among mild cognitive impairment individuals often makes it challenging to document case reports clinically. Additionally, data on the Indian population is also limited. Therefore, our study includes a case study of a 56-year-old male with mild cognitive impairment from our Institute. A patient had symptoms of mild cognitive impairment following a stroke that occurred 23 years back (vascular in origin). Both formal and informal assessments were carried out. Formal testing was done using the Montreal Cognitive Assessment. On assessment of memory, mild deficits in working memory, episodic memory, and procedural memory were noticed. Attention span and Word-finding difficulties with reduced use of words were observed in language assessment. Problems in reasoning, problem-solving, and decision-making skills, indicating deficits in executive functioning were evident. Linguistic deficits presenting secondary to cognitive deficits in our client could have led to communication breakdowns in speech, affecting his overall quality of life.